Partai Politik Sebagai Political Brand - Fajar Febriansyah; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Safira Hasna (Cakrawala - Jurnal Humaniora, 2021)
Nowadays, political parties need a political marketing strategy that is considered to be able to increase the number of votes, especially for certain candidates of political parties. Marketing elements can be adopted in political parties, especially when doing branding. Therefore, the objective of this research is to determine the influence of brand elements in politics such as brand communication, brand image, brand trust, and brand loyalty to political parties, namely Partai Amanat Nasional (PAN). The research shows that there is no effect of brand communication on brand image and brand trust. And there is no influence of brand image on brand trust. As for the element of trust, there is an effect of brand trust on PAN brand loyalty with a low percentage of 14.7%. When someone has given confidence in a certain political party, they have guaranteed that the program given by that party is the best for the public, so that someone will be consistent in choosing the same party in the future during the election or loyal to political parties.